The Effect of Deep Learning on Critical Thinking Skills of Grade VIII Students at UPT SMPN 2 Mangarabombang Takala - Surajuddin; Nurhayati B; Muhiddin Palennari; Firdaus Daud; Ismail (Jurnal Penelitian Pendidikan IPA, 2026)
In today's era of digital transformation and global uncertainty, education is no longer simply about transferring knowledge, but rather about equipping students with 21st-century competencies. One of the most crucial competencies is critical thinking skills. This ability enables students to objectively analyze information, evaluate arguments, and formulate creative solutions to complex problems. This study aims to determine the effect of deep learning on the critical thinking skills of eighth-grade students at UPT SMPN 2 Mangarabombang Takalar. This study used a quantitative quasi-experimental method using a non-equivalent control group design. The study population included all eighth-grade students at UPT SMPN 2 Mangarabombang. A simple sampling technique was used, selecting 23 students from class VIII B as the experimental class with deep learning and 23 students from class VIII C as the control class with conventional learning. The instruments used included a learning activity observation sheet and a critical thinking skills test based on Robert Ennis's indicators. Data were analyzed using descriptive and inferential statistics. The t-test results for critical thinking skills showed a significance value of 0.01, which is less than α = 0.05. The results of this study concluded that there was an influence of in-depth learning on the critical thinking skills of class VIII students at UPT SMPN 2 Mangarabombang Takalar.